China's Global Rebalancing and the New Silk Road (Springer Singapore, 2018)
This collaborative volume discusses the One Belt One Road, or the New Silk Road, initiative of Chinese President Xi Jinping from the perspectives of the Belt and Road countries. This initiative has been viewed as a re-globalization drive by China in the backdrop of financial crisis of the West and the latter's increasingly protectionist tendencies of late. Rather than 'rebalancing' towards a certain region, this is supposed to be China's 'global rebalancing' aimed at inclusiveness and a win-win partnership. The initiative has raised hopes as well as suspicions about China's goals and intentions; that is, whether this is in sync with China's foreign policy goals, such as multipolarity, no hegemonic aspirations, and common security, or if this is an antidote to the U.S. foreign policy goals in the region, and China's ambition to realizing its long-term vision for Asian regional and global order. In this volume, a galaxy of eminent academics from India, China, Pakistan, Uzbekistan, Germany and Southeast Asia have critically analysed every aspect of this mammoth project, including the six major economic corridors identified by China for policy coordination, infrastructure connectivity, unimpeded trade, monetary circulation, and people to people exchanges. The authors have interpreted China's peripheral, regional as well as global diplomacy both over land and sea. This topical volume is of interest to scholars and students of Asian studies, China studies, Asian history, development studies, international relations and international trade. .